Pemasaran Agroindustri Kopi Biji Salak di Kabupaten Jember - Ambar Asri Candra Putri; Ebban Bagus Kuntadi (UPT Penerbitan Universitas Jember, 2018)
The aim of this research is to discover segmentation marketing of salak seed coffee in Jember. The method of research area determinated by purposive method at Primadona Kampus, Primadona Trunojoyo, Prima Rasa Gajahmada, Toko Sumber Madu and Sari Rasa Trunojoyo with consideration UD. Koplak Food able to send 17-25 box salak seed coffee/month. Sampling method determinated by convenience sampling. Data collected by interview and documentation study. Data analysis method for geographic, demographic, behavioral segmentation are using descriptive method and for psychographic segmentation is by using skala likert, validation test, reliability test, tabulation analysis and percentage analysis. The result show that based on geographic segmentation, consumers are from Jember and buy Koplak at Pusat Oleh-Oleh Primadona Kampus. Based on demographic segmentation, their gender are male, age 35-41 years old, married, have 3 family burdens, education background are senior high school, the profession are PNS, income/month Rp.1.500.000-2.500.000 and outcome/month ≤Rp 1.500.000. Based on behavioral segmentation, Koplak known from Pusat Oleh-Oleh Jember, buying motivation are curiousity, consumption time around 0-7 months, consumption intensity 1-2 glass/week, buying Koplak without any plan and they didn’t buy a different beverage if Koplak doesn’t available. Based on psychographic segmentation, consumers are people that following a trend and life style, like to try something new and has consumtif behavior.